Contested Common Space, Regulation and Inclusion at the Coogee Women's Pool. Issue 2 (September 2022) - Morgan, Bronwen; Goldblatt, Beth
Abstract : This article concerns two disputes that occurred between 2020–22 at the Coogee Women's Pool, a public ocean pool in Sydney reserved for use only by women. One contest concerned the governance of the pool by its Management Committee related to differing conceptions of the ethos of the pool and the nature of its custodianship. The other concerned the exclusion of trans women from the pool over the definition of 'women' allowed access to the facility. The article examines these disputes and the contests they generated in exploring when and how forms of law encourage or undermine relational regulation in the context of community-controlled public space. It draws on ideas about the commons elaborated by Silvia Federici and the concept of ethos articulated by Ivan Illich to understand the nature and value of community-controlled public space. The article links these ideas to the role of law in engaging with scholarship on the right to the city and rights to protest in relation to the commons. It draws on this framing, and uses interviews, primary and secondary sources, to closely study the recent history at the Women's Pool regarding governance of common space and issues of inclusion within the space. In looking at how law was used in relation to both aspects, it finds the idea of relational regulation helpful. The article suggests that light touch relational regulation might support the ethos of managed communal spaces, making room for deliberative practices that facilitate the resolution of challenging questions of membership and participation. The events in this small space of recreation prefigure possibilities for deliberation, care and (re)enchantment as a counter to neoliberal ordering.